Impact of the construction of a dam and spur dikes on the hydraulic habitat of Megalobrama terminalis spawning sites: A case study in the Beijiang River (China) - Xiyan Yang; Shanghong Zhang; Wenda Li; Caihong Tang; Jin Zhang; Sebastian Schwindt; Silke Wieprecht; Taiwei Wang (Ecological Indicators, 2022)
Water conservancy projects may result in considerable economic and social benefits, though there is widespread concern about how their impact on aquatic ecosystems. However, there is no study about the combined effects of typical hydraulic structures (a dam and numerous spur dikes) on hydraulic habitat conditions. This is why the impacts of the construction of a dam and spur dikes in a reach of the Beijiang River between the Feilaixia and the Qingyuan on fish hydraulic habitat conditions are assessed. A habitat suitability model was established by coupling a two-dimensional (2-D) hydrodynamic model with habitat suitability curves. The coupled model then was used to simulate the spawning sites of Megalobrama terminalis (M. terminalis), calculate the usable habitat area (UHA), identify the spatial distribution of suitable spawning ground in the river reach, and analyze the habitat quality and hydraulic habitat diversity. The results show that the dam alone would negatively impact fish habitat, and cause the UHA to decrease by 35.5 % on average. The high-quality habitat area and the hydraulic habitat diversity decreased because of the dam. The spur dikes had positive effects and increased the UHA by 13.9 % on average. In addition, spur dikes increased the high-quality habitat area and enhanced the hydraulic habitat diversity. The lateral discontinuity resulting from spur dikes (the rate of UHA change, RC = 13.9 %) had less impact on the fish hydraulic habitat than the longitudinal discontinuity impact resulting from the dam construction (RC =  − 35.5 %). The spur dikes and a dam (RC = 21.94 %) resulted in a more significant improvement effect on the habitat conditions than the spur dikes without a dam (RC = 5.84 %). The dam and spur dikes in combination resulted in better outcomes regarding hydraulic habitat conditions than spur dikes alone, and the spur dikes reduce the ecological stress caused by the dam. The insight from this study can serve as a reference for engineers and scientists who are considering similar river regulation and ecological restoration initiatives aimed at a steady flow pattern that are advantageous for a specific fish species and lifestage.